2007
DOI: 10.1002/cbm.653
|View full text |Cite
|
Sign up to set email alerts
|

Does PTSD occur in sentenced prison populations? A systematic literature review

Abstract: All four papers suggested that the prevalence of PTSD among sentenced prisoners is higher than that in the general population, as reported elsewhere. Overall the findings suggest a likely need for PTSD treatment services for sentenced prisoners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
115
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(127 citation statements)
references
References 71 publications
3
115
2
3
Order By: Relevance
“…Such sub-threshold posttraumatic stress is clinically relevant, as it associated with significant and long-standing impairment (Marshall, Olfson, Hellman, et al, 2001). Although few studies have examined the prevalence of PTSD among offender samples, a recent systematic review found it to be more prevalent among prisoners than in the general population with a rate of between 4 and 21% (Goff, Rose, Rose, & Purves, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Such sub-threshold posttraumatic stress is clinically relevant, as it associated with significant and long-standing impairment (Marshall, Olfson, Hellman, et al, 2001). Although few studies have examined the prevalence of PTSD among offender samples, a recent systematic review found it to be more prevalent among prisoners than in the general population with a rate of between 4 and 21% (Goff, Rose, Rose, & Purves, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the high levels of recidivism and on available research literature, such a claim is undeniable. A comprehensive literature review suggested that the previously assumed 2% PTSD rate of prison inmates is actually a 21% (Goff, Rose, Rose, & Purves, 2007). In a study on female inmates in Illinois, 60% of the 217 sample fulfilled the criteria for PTSD (Reichert & Bostwick, 2011).…”
Section: Incarcerationmentioning
confidence: 99%
“…For instance, incarcerated older adults are considered at the highest risk for victimization because of their decreasing ability to defend themselves against younger prisoners or staff (Dawes, 2009). Along the same lines older adults in frail health are at higher risk of all forms of elder abuse, which could include sexual assaults, in prison (Goff et al, 2007;Stojkovic, 2007). Furthermore, older adult offenders also have additional age specific stressors, such as concerns over failing health and the fear of dying in prison (Aday, 2006;Marushak, 2008), in addition to the physical vulnerabilities presented by the aging process.…”
Section: Sexual Abuse Among Older Adults In Prison and The Communitymentioning
confidence: 99%